Analysis of metabolic differences in maize in different growth stages under nitrogen stress based on UPLC-QTOF-MS - Song, Guipei; Lu, Yanli; Wang, Yuhong; Nie, Caie; Xu, Mengze; Wang, Lei; Bai, Youlu (Frontiers in Plant Science, 2023)
The metabolic changes are the basis for rational nitrogen nutrition regulation in maize. To explore the changes of different metabolites and their metabolic pathway in maize leaves under nitrogen stress, it was analyzed that the maize leaves under different nitrogen treatments and in three key fertility periods using metabolomics. The results showed that nitrogen stress significantly affected sugar metabolism and nitrogen metabolism, and affected carbon and nitrogen balance, and the effects of stress on maize leaves metabolism increased with the growth process. Metabolic pathways such as the TCA cycle and starch and sucrose metabolism were mainly affected at the seeding stage (V4). The stress response to nitrogen deficiency also showed significant upregulation of flavonoids such as luteolin and astragalin during the booting stage (V12) and anthesis-silking stage (R1). During R1 stage, the synthesis of tryptophan and phenylalanine and the degradation of lysine were significantly affected. Compared with nitrogen stress, the metabolic synthesis of key amino acids and jasmonic acid were intensified and the TCA cycle was promoted under nitrogen sufficiency conditions. This study initially revealed that the response mechanism of maize to nitrogen stress at the metabolic level.